Measures for Assessing Basic Education in the Philippines - Dalisay S. Maligalig; Jose Ramon G. Albert (Philippine Institute for Development Studies (PIDS), 2008)
The second goal of the Millennium Development Goals (MDGs) is to achieve universal primary education. The target is to reach all the MDGs by 2015. Trends in education indicators for monitoring the second MDG suggest that Philippines may probably not meet the target on achieving universal primary education. Indicators that monitor gender disparity in primary and secondary education suggest that females are at an advantage over males. In this paper, various education indicators sourced from administrative reporting systems and surveys are looked into for assessing basic education in the country. Issues on the lack of comparability of figures from reporting systems, on the need to improve dissemination of education statistics, and on the need to properly link data with policy through a systematic monitoring and evaluation system are also discussed.
Keywords: 330; millennium development goals (MDG); education indicators; monitoring and evaluation; UN-Entwicklungsziele; Allgemeinbildende Schule; Philippinen